Review on comparative efficacy of bevacizumab, panitumumab and cetuximab antibody therapy with combination of FOLFOX-4 in KRAS-mutated colorectal cancer patients - Pathak, Surajit (Oncotarget, 2017)
Colorectal cancer, fourth leading form of cancer worldwide and is increasing in alarming rate in the developing countries. Treating colorectal cancer has become a big challenge worldwide and several antibody therapies such as bevacizumab, panitumumab and cetuximab are being used with limited success. Moreover, mutation in KRAS gene which is linked with the colorectal cancer initiation and progression further interferes with the antibody therapies. Considering median progression free survival and overall survival in account, this review focuses to identify the most efficient antibody therapy in combination with chemotherapy (FOLFOX-4) in KRAS mutated colorectal cancer patients. The bevacizumab plus FOLFOX-4 therapy shows about 9.3 months and 8.7 months of progression free survival for KRAS wild and mutant type, respectively. The overall survival is about 34.8 months for wild type whereas for the mutant it is inconclusive for the same therapy. In comparison, panitumumab results in better progression-free survival which is about (9.6 months) and overall survival is about (23.9 months) for the wild type KRAS and the overall survival is about 15.5 months for the mutant KRAS. Cetuximab plus FOLFOX-4 therapy shows about 7.7 months and 5.5 months of progression-free survival for wild type KRAS and mutant type, respectively. Thus, panitumumab shows significant improvement in overall survival rate for wild type KRAS, validating as a cost effective therapeutic for colorectal cancer therapy. This review depicts that panitumumab along with FOLFOX-4 has a higher response in colorectal cancer patients than the either of the two monoclonal antibodies plus FOLFOX-4.